Development of a rotary mechanism with manual feeding for husking coconut - GUBASH AZHIKODAN RAJESH A.N EDWIN BENJAMIN; Jippu Jacob (Guide) (Tavanur 2008 Kelappaji College of Agricultural Engineering and Technology)
Development of a rotary mechanism with manual feeding for husking coconut
Development of a rotary mechanism with manual feeding for husking coconut